The Effect of Company Size, Profitability and Audit Committee on Audit Delays in Property and Real Estate Companies Listed on the Indonesian Sharia Stock Index (ISSI) in 2022-2024 - Sribatul Islambiah; Rofiqoh Ferawati (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to analyze the influence of company size, profitability, and audit committee on audit delays in property and real estate companies listed on the Indonesian Sharia Stock Index (ISSI) in 2022–2024. Audit delay is the time difference between the closing date of the company's financial year and the date of issuance of the audit report, which reflects the timeliness of the delivery of financial information to stakeholders. This study uses a quantitative approach with the purposive sampling method, so that a sample of companies that have experienced delays in publishing annual financial statements during the research period is obtained. The data used is secondary data in the form of annual financial statements obtained from the Indonesia Stock Exchange. The data analysis technique used was multiple linear regression analysis with the help of statistical software, namely Eviews 12. The results showed that partially company size, profitability and audit committee had no effect on audit audit while simultaneously company size, profitability and audit committee had an effect on audit delay. Thus, the results of this study are expected to provide empirical evidence regarding the factors that affect audit delays and become a consideration for company management in improving the timeliness of financial reporting. In addition, this research is also expected to be a reference for investors and related parties in making economic decisions based on sharia principles.